Neurodiversity in Saudi Arabia: Towards quality education and reduced inequalities [version 2; peer review: 1 approved, 2 approved with reservations] - Borey Be; Alex S. M. Mhone; Ahmed Alduais; Ahmed Yahya Almakrob (F1000Research)
Traditional educational frameworks in Saudi Arabia have historically adopted a deficit-based approach to special education, potentially overlooking the benefits of neurodiversity. As global educational paradigms shift toward inclusive practices, examining the alignment of Saudi special education laws with neurodiversity principles becomes crucial. This content analysis study aimed to explore the existing literature on special education in Saudi Arabia to ascertain whether the laws and policies support or hinder the practice of neurodiversity, a concept that is gaining international recognition but remains nascent in Saudi Arabia. A systematic literature search was performed in Web of Science and Scopus, yielding 21 relevant studies after screening and application of inclusion criteria. A content analysis was conducted, focusing on the categorization of data relevant to special education laws and their implications for neurodiversity. The analysis identified seven key categories, including Implementation of Inclusive education and transition services, that reflect the current state of special education laws in relation to neurodiversity. A conceptual model was developed, illustrating the potential of special education laws to both support and impede neurodiversity in Saudi Arabia and potentially worldwide.